Influence of barley non-starchy polysaccharides on selected quality attributes of sponge cakes. (November 2017) - Moza, Jessy; Gujral, Hardeep Singh
Abstract: In this study, the suitability of refined flours from different hulless barley cultivars for making sponge cakes was investigated and was compared with refined wheat flour cake in terms of selected quality attributes like mixolab properties, batter viscosity, crumb image characteristics, cake volume, texture and sensory acceptability. The content of total β-glucan and arabinoxylans ranged between 3.4 to 4.4% and 0.7–1.1% for refined barley flours and it significantly increased the viscosity, slurry consistency and gelatinization time (p ≤ 0.05) of cake batters. Lower protein (6.9–10.3%) and higher non-starchy polysaccharide contents of barley flours promoted formation of small sized air cells in cakes which impacted the crumb characteristics significantly. In terms of end product acceptability, the barley cakes displayed higher cake volumes and exhibited springiness and cohesiveness values significantly similar (p ≤ 0.05) to wheat cake. It was revealed that batters showing a higher mixolab peak viscosity displayed greater cake hardness (R = 0.74, p ≤ 0.05) and chewiness (R = 0.71, p ≤ 0.05) values upon texture analysis. Altogether, hulless barley refined flours displayed good cake making performance and could be used to make sponge cakes which are equivalent in quality to wheat flour cake but at the same time deliver high levels of bioactive compounds. Highlights: Cake batter consistency correlated with the flour β-glucan and arabinoxylan contents. β-glucan and arabinoxylans increased cake cell density and produced uniform crumb. Low protein flours led to formation of cakes with small sized air cells. Batters with lower C3 value produced good quality cakes.